Disturbance of Mangrove Forest Due To Climate Change: The Prospects of Sundarban - Gupta, Shimul (Future Science / FSH-PH Publications, 2021)
Mangrove forest has a significant importance in protecting natural disaster, environmental sustainability and in local economy. In Bangladesh, only mangrove forest Sundarban also servicing for environmental sustainability, protecting tropical cyclone, local employment generation and so on. Thus, its natural properties are being hampered through people involvement and natural calamities. Moreover, Rapid population growth and climate change stimulating these disturbances of natural properties of Sundarbans. This paper aim at how climate change is disturbing mangrove forest in Bangladesh and how this disturbance may be threatful for future environmental sustainability. Interrelation between climate change and disturbance of Sundarbans has been established through various exiting literature review and for quantifying the amount of disturbance remote sensing data has been applied and future threat of environmental sustainability has been assessed by comparing regeneration capacity of Sundarban after a tropical cyclone and amount of disturbance by a tropical cyclone. Result found that climate change increasing the frequency of natural calamities and affecting significantly on mangrove forest due to its complex bio-diversity and strategic location before regeneration of disturbance. On the other hand, threat of mangroves as well as environment is associated with temperature rising, ice melting and sea level rising are increasing because of frequent occurrence, magnitude as comparing with regeneration capacity.